Measurement of β−-decay continuum spectrum of 138La. (15th June 2015) - Giaz, Agnese; Gosta, Giulia; Camera, Franco; Riboldi, Stefano; Blasi, Nives; Bracco, Angela; Brambilla, Sergio; Million, Benedicte
Abstract: The LaBr3 :Ce scintillator offers the unique opportunity to study the β − radioactive decay of 138 La. The 138 La isotope is one of the rarest isotopes on Earth (it is present as 0.09% in natural lanthanum) and because of its extremely long lifetime, of the order of 10 11 years, large amounts of 138 La are needed for the measurement of the β − -decay spectrum. In the literature, only one dedicated experimental measurement is present and the results seem not to be reproduced by the nuclear theory. A second measurement of the β − continuum spectrum is presented in this work. For this measurement, two LaBr3 :Ce scintillators and two different experimental techniques were used. The shape of the β − continuum spectrum, measured down to the energy of 10 keV, is found to be very similar to the one previously measured and published, but it is different from the theoretical published spectrum.